Transient convective heat transfer - Padet,J. (2005)
In nature, as well as within the human-made thermal systems, the time-variable regimes are more commonly encountered, if not always, than the permanent regimes. Nevertheless, studies in convection are still more frequent in the permanent regimes, undoubtedly due to the related difficulties in calculation in terms of time and cost of computation. One may distinguish two categories of time-dependent transfers: those which are due to external causes (variable boundary conditions) and those that are due to internal causes (sources of variable power, instabilities, turbulence), and the combination of these two types may also be encountered. In this presentation, we shall analyze some situations which belong to the first category. These are concerned with: - a group of boundary layer flows in forced, natural or mixed convection, where the wall is subjected to time-variable conditions in temperature or flux. - another group of fluid flows within ducts, in laminar mixed convection regime, where the entry conditions (mass flow rate, temperature) are time-dependent. The techniques of analysis are mainly extensions to the differential method and to the integral method of Karman-Polhausen in boundary layer flows, and the finite differences solution of the vorticity and energy equations for internal flows. The results presented in the transient state are caused by steps of temperature, heat flux or velocity, and in particular show the time evolution of the dynamic and thermal boundary layers, as well of the heat transfer coefficients. Three examples of applications will then be treated: the active control of convective transfers, the measurement of heat transfer coefficients, and the analysis of heat exchangers. The main idea in the active control is that of managing the temperatures or heat fluxes by employing a variable regime. Under certain conditions, this procedure may reveal itself quite interesting. The measurement of transfer coefficients by the photothermal impulse method possesses a great interest since it is performed in a non-intrusive way without contact. However, in order to be precise, it needs to account for the thermal boundary layer perturbation due to the radiative flux sent over the surface, which means to know the evolution of the transfer coefficient during the measurement. Previous studies therefore provide essential information. Within the domain of heat exchangers, we shall present a different global method, which allows for the evaluation of the time constant of an equipment in response to sample variations of temperature or mass flow rates at the entrance. In conclusion, a brief balance of the ICHMT Symposium "Transient heat and mass transfer", Cesme, Turkey, August 2003, will be presented.